Study on the optimal scheme of shale complex cracks formation based on Xsite discrete lattice method. - Haoyong Huang; Guozhou Qiu; Jianfa Wu; Yintong Guo; Shuai Cui; Zhen Zhang (PLoS ONE)
In the contemporary energy industry, shale gas, as an important unconventional energy resource, has been widely concerned. However, the exploitation of shale gas is faced with complex geological conditions and technical challenges, one of the main challenges is that it is difficult to form discrete complex crack networks in shale, which greatly reduces the recovery rate. For different geological conditions and engineering needs, the criteria for evaluating the effect of reservoir reconstruction will be different. The XSite discrete lattice method can simulate the crack development process and provide detailed crack morphology and characteristic information (crack area, crack volume, etc.). The advantage of the orthogonal experimental design scheme is that it can obtain as much information as possible in a relatively small number of tests, improving the efficiency and cost effectiveness of the test. Therefore, based on Xsite design 6 factor 5 horizontal orthogonal test, this paper obtained the optimal fracturing design scheme with crack area, crack shape volume, tensile crack area and shear crack area as evaluation criteria. The standard deviation of each influencing factor was calculated to obtain the optimal fracturing scheme under different evaluation criteria. And considering a variety of quantitative indicators, calculate the influence weight of each influencing factor, and get the optimal fracturing scheme considering a variety of evaluation basis. Two Wells with different depth and natural fracture development were selected to verify the feasibility of orthogonal simulation test by changing fracturing fluid rate. To provide scientific basis and technical support for optimizing shale gas exploitation scheme.